Does dexamethasone affect hepatic CYP450 system of fish? Semi-static in-vivo experiment on juvenile rainbow trout - Burkina, Viktoriia; Sakalli, Sidika; Rasmussen, Martin Krøyer; Zamaratskaia, Galia; Koba, Olga; Thai, Giang Pham; Grabic, Roman; Randak, Tomas; Zlabek, Vladimir (Chemosphere, 2015)
Effects of aquatic pollutants on fish are of increasing concern. Pharmaceutical-based contaminants are prioritized for further study in environmental risk assessment using several approaches. Dexamethasone (DEX) was one such contaminant recognised for its effect on fish health status. Thus, we carried out an in vivo experiment to identify potential effects of DEX on rainbow trout. Fish were exposed to 3, 30, 300 and 3000ngL(-1) DEX in a semi-static system over a period of 42d. The concentrations of DEX that fish were exposed to was confirmed by LC-LC-MS/MS. Using hepatic microsomes, we determined cytochrome P450 content, activities of ethoxyresorufin O-deethylase (EROD), p-nitrophenol hydroxylase (PNPH), 7-benzyloxy-4-trifluoromethylcoumarin O-debenzylase (BFCOD) and benzyloxyquinoline O-debenzylase (BQOD), as well as protein expression. Our results showed that fish do not change the catalytic activity of CYP450-mediated reactions after high DEX concentration exposure. These results disagree with mammalian studies, where DEX is a well-known inducer of CYP450. We showed a significant effect of DEX exposure on CYP450-mediated reactions (EROD, BCFOD, BQOD and PNPH) when expressed as amount of product formed per min per nmol total CYP450 at 3, 30 and 300ngL(-1) after 21d exposure. Moreover, BFCOD and BQ activities showed matching trends in all groups. Western blot analysis showed induction of CYP3A-like protein in the presence of the lowest environmentally relevant concentration of DEX. Based on these findings, continued investigation of the effect of DEX on fish using a battery of complementary biomarkers of exposure and effect is highly relevant.
Keywords: jaterní mikrozomy; Animals; vztah mezi dávkou a účinkem léčiva; Dexamethasone; Oncorhynchus mykiss; zvířata; Dose-Response Relationship, Drug; tandemová hmotnostní spektrometrie; chemické látky znečišťující vodu; Water Pollutants, Chemical; dexamethason; Cytochrome P-450 Enzyme System; systém (enzymů) cytochromů P-450; cytochrom P-450 CYP1A1; Cytochrome P-450 CYP1A1; Microsomes, Liver; Tandem Mass Spectrometry